Sociocultural Reproduction in the Midst of Urban Modernization: An Anthropological Study of the Politics of Space in Ketandan Village Surabaya City - Geraldy, Galang; Budi, Dwi Windyastuti; Asfar, Muhammad (The Sunan Ampel Review of Political and Social Sciences, 2024)
Ketandan Village is one of the oldest villages located right in the middle of the modernization of the city such as hotel buildings, office centers and trade on Embong Malang, Tunjungan, Praban and Genteng Kali roads. This area is often referred to as the golden quadrilateral of Surabaya's economic growth. In the context of spatial anthropology, the existence of the old village actually has a very strong sociocultural foundation, especially if it is then associated with the presence of the An-Nur Mosque building, the Tomb of Mbah Buyut Tondo and the Joglo Cak Markeso Cultural Hall in the middle of the village. The momentum to develop this cultural capital emerged in 2016 when the revitalization of Joglo Cak Markeso as a pilot project of the Global Public Space Programme (GPSP) and the issuance of the Mayor's Decree related to the status of Ketandan tourism village in 2020. Through the perspective of the political anthropology of space, the spatial aspect is not only measuring technical-material matters but also intertwined with the content of values, knowledge and ideology that affect the social life of the community. The problem is that the cultural construction that is formed is still artificial and procedural, which does not reach the anthropological aspects of space. Spatial practices are incidental and do not become social rituals that encompass daily life. This means that the historic building does not work in the political anthropology of space or move into the political economy of cultural capitalization. This anomaly is a sign that there is cultural disorientation due to weak sociocultural attachment to spatial practices and the determination of urban modernization.